Development of ultra-high strength Ti-Nb-Sn alloys through grain-refinement by in situ Zener pinning. (September 2022) - Church, NL; Talbot, CEP; Wise, GJ; Shah, OYI; Jones, NG
Abstract: Metastable β-Ti alloys based on the Ti-Nb system are of commercial interest as they undergo a reversible martensitic transformation that offers damping capabilities. However, their use is currently limited by a low yield stress compared to other alternatives such as NiTi. Here, we show how this limitation can be overcome by the in situ formation of the Ti3 Sn phase concurrent with recrystalisation. The Zener pinning resulting from the Ti3 Sn precipitates provides significant Hall-Petch strengthening leading to a yield stress in excess of 1 GPa, more than double that of similar alloys, whilst still allowing conventional processing routes. This has the potential to provide Ti-Nb yield stresses that can rival those of NiTi, addressing one of the biggest challenges for this class of alloys. Graphical abstract: Image, graphical abstract